Distribution and Identification of Sources of Heavy Metals in the Voghji River Basin Impacted by Mining Activities (Armenia) - Gabrielyan, A. V.; Minasyan, S. H.; Shahnazaryan, G. A. (Journal of chemistry, 2018)
The objective of this research is to assess the distribution of heavy metals in the waters and sediments of the Voghji River and its tributaries impacted by mining activity and to reveal the real source of each of the heavy metals in the environment for assessing the pollution level of heavy metals. Voghji River with two main tributaries (Geghi and Norashenik) drain two mining regions. To identify distribution and pollution sources of heavy metals, the water and sediment samples were collected from eight sampling sites. The results of statistical analysis based on data sets of the period 2014–2016 showed that, after the influence of drainage water and wastewater of mining regions, heavy metal contents in the Voghji River basin dramatically increased. The waters of the Voghji River were highly polluted by Mn, Co, Cu, Zn, Mo, Cd, and Pb. The relation of metals content was highly changed due to anthropogenic impact disturbing the geochemical balance of the Voghji River. The water quality based on only heavy metal contents in the source of the Voghji River belongs to “good” chemical status, and in the sources of Geghi and Norashenik Rivers it is “moderate.” The water quality of Voghji and Norashenik Rivers is sharply worsening after the influence of mining activity, becoming “bad” chemical status. The research revealed the pollution sources of each metal.